Desempeño docente en una institución educativa policial de la Región Callao - Juárez Echevarria, Angélica (2012)
The research is descriptive simple with a non experimental cross sought to determine the performance level of secondary teachers according the teachers, the students and the vice- principal in an Educational Police Institution in Callao Region -2009. The sample selection is nonrandom. Three instruments were applied developed by Ministry of education of Peru, adapted by the author and validated by experts using V Aiken with a high level of validity and reliability, designed for 22 teachers from the Ministry of Interior, Ministry of Education and APAFA, for 150 students and for the vice- principal. Three dimensions are measured; they are educational work planning, management of teaching and learning process and professional responsibilities. The results disclose a good performance as teachers with 59, 1%, students with 73, 3% and the vice principal with 59, 1%. Concluding there is a high tendency to have good levels of performance.